Commune centre, agglomération, aire urbaine : quelle pertinence pour l’étude des villes ? - Marianne Guérois; Fabien Paulus (Cybergeo, 2002)
Several official definitions of the city have been created in France since 1950 in order to fit the evolution of the urbanization process. The choice of one perimeter among others may influence urban studies and the production of urban indicators.